2019
DOI: 10.1186/s13046-019-1241-9
|View full text |Cite|
|
Sign up to set email alerts
|

Minichromosome maintenance 3 promotes hepatocellular carcinoma radioresistance by activating the NF-κB pathway

Abstract: Background Hepatocellular carcinoma (HCC) is the most common tumors in the worldwide, it develops resistance to radiotherapy during treatment, understanding the regulatory mechanisms of radioresistance generation is the urgent need for HCC therapy. Methods qRT-PCR, western blot and immunohistochemistry were used to examine MCM3 expression. MTT assay, colony formation assay, terminal deoxynucleotidyl transferase nick end labeling assay and In vivo xenograft assay were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 41 publications
(30 reference statements)
2
35
0
Order By: Relevance
“…5d). Among the most significant genes we identified SKP2, IRF2 and MCM3, all related to tumor progression and metastases [33][34][35]. In agreement with these shared cues, 5 signaling pathways (MAPK, JAK-STAT, p53, VEGF and PI3K) that were not significantly different between immunosuppressive monocytes and tumoreducated monocytes, were observed; however, we found other signaling pathways uniquely upregulated in suppressive monocytes NF-κB, TGFβ, TNFα, Hypoxia, TRAIL and EGFR (Additional file 1: Figure S5D).…”
Section: Circulating Monocytes From Pdac Patients Induce a Stronger Tmentioning
confidence: 99%
“…5d). Among the most significant genes we identified SKP2, IRF2 and MCM3, all related to tumor progression and metastases [33][34][35]. In agreement with these shared cues, 5 signaling pathways (MAPK, JAK-STAT, p53, VEGF and PI3K) that were not significantly different between immunosuppressive monocytes and tumoreducated monocytes, were observed; however, we found other signaling pathways uniquely upregulated in suppressive monocytes NF-κB, TGFβ, TNFα, Hypoxia, TRAIL and EGFR (Additional file 1: Figure S5D).…”
Section: Circulating Monocytes From Pdac Patients Induce a Stronger Tmentioning
confidence: 99%
“…In rat models of ALF, DNA replication is essential for hepatic regeneration [ 18 ]. MCM3, a key component of the heterohexameric minichromosome maintenance (MCM) complex, plays an important role in mammalian DNA helicase activity and the initiation of DNA replication [ 24 ]. Similarly, CDK4 plays a key role in cell proliferation, particularly during the progression of cells from the G1 to S phase of the cell cycle [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conformity to their crucial roles in replication, MCM genes are determined as potential prognostic indicators for cancers [10,11] . Previous studies have found that genetic up-regulation or ampli cation of several MCM proteins including MCM2, MCM3, MCM6 and MCM7 can promote cell proliferation and HCC tumorigenicity [12][13][14][15] . However, research on the role of MCM10 in HCC is scarce.…”
Section: Introductionmentioning
confidence: 99%